Exploring the Role of Geometry Understanding and Spatial Ability in Academic Achievement: The Moderating Effect of Self-Confidence - Aswani, Andi; S, Agustan; Mukhlis, Mukhlis (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study investigates the impact of understanding geometry concepts, spatial ability, and self-confidence on student learning outcomes. Understanding geometry enhances mathematical logic, spatial ability strengthens spatial comprehension, and self-confidence boosts learning motivation. Collectively, these variables are crucial for improving student learning outcomes. The research employed an explanatory design, conducted in two elementary schools within the same cluster. A random sampling method selected samples from one class of an Elementary School in Panyikokkang with 21 students and another class with 23 students, resulting in a total of 44 students. Data collection instruments included a validated Self-Confidence questionnaire, Geometry Concept Understanding test, Spatial Ability test, and a Student Learning Outcomes test derived from daily quizzes on geometry topics. Data were analyzed using Inferential Statistical Analysis and Moderated Regression Analysis (MRA). The Moderated Regression Analysis (MRA) revealed that self-confidence acts as a quasi-moderator in the relationship between understanding geometry concepts and learning outcomes. Specifically, students with higher self-confidence showed a better understanding of geometry concepts, positively influencing their learning outcomes. However, self-confidence did not moderate the effect of spatial ability on learning outcomes. These findings highlight the importance of understanding geometry concepts in enhancing students' comprehension of geometry and developing spatial abilities at the elementary level. The results suggest that self-confidence plays a significant role in mediating the relationship between understanding geometry concepts and learning outcomes but not between spatial ability and learning outcomes. The study underscores the necessity for educators to focus on understanding geometry concepts and fostering self-confidence to design effective learning strategies that improve student achievement in mathematics, particularly in geometry.